Screening Kadar Rheumatoid Factor (RF) Pada Lanjut Usia (Lansia) Dengan Keluhan Nyeri Sendi - Adrianus Ola Wuan; Marni Tangkelangi; Wilhelmus Olin; Michael Bhadi Bia; Ni Ketut Yuliana Sari (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Rheumatoid arthritis is an autoimmune disease that occurs when the body's immune system mistakenly attacks healthy joints. The disease can start at any age, but the likelihood of onset is highest in older adults. In Rheumatoid Arthritis the tissue lining the joints becomes thickened resulting in swelling and pain. Elderly is an age that has a greater possibility of having an autoimmune this is based on the statement that the older you are, the greater the chance of having an autoimmune. Early diagnosis and treatment isthe key to successful treatment of Rheumatoid Arthritis because joint damage cannot be restored once it occurs. Rhematoid Factor examination is largely used to help diagnose rheumatoid arthritis. Community service activities aim to determine the description of RF levels in the elderly with supply disorders, descriptive research type with a cross sectional approach. The sampling technique used purposive sampling as many as 62 elderly people in the Social Service of NTT Province. The results of RF examination in all elderly samples 6.45% have positive results and 93.55% negative results.